Effectiveness of polymyxin B hemoperfusion in acute exacerbation of interstitial pneumonia: a retrospective analysis: Polymyxin B and interstitial pneumonia - Lee, Song-I (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background Acute exacerbation (AE) of interstitial pneumonia (IP) occurs commonly and has a poor prognosis. Polymyxin B hemoperfusion (PMX-DHP) has a beneficial effect on AE of some types of IPs, particularly idiopathic pulmonary fibrosis (IPF). However, little is known about the efficacy of PMX-DHP in the Korean population. The aim of this study was to examine the effectiveness of PMX-DHP in AE of IP. Methods We conducted a retrospective study of 12 patients with AE of IP, including two patients with AE of IPF, who were treated with PMX-DHP at our center. Treatment with PMX-DHP was carried out once or twice. We collected and analyzed data on changes in oxygenation with PMX-DHP and survival after AE. Results In patients with AE of IP, the ratio of partial pressure of arterial oxygen to the fraction of inspired oxygen, or the P/F ratio, had significantly improved at the end of the treatment with PMX-DHP (87.0 [80.3–130.9] to 200.6 [105.0–245.5] mmHg, p = 0.019). The white blood cell (WBC) count had significantly reduced at the end of the treatment (12,400 [8,860–20,287] to 6,800 [3,950–15,775]/mm3, p = 0.050). The 28-day and in-hospital mortality rates of patients after AE of IP were 41.7 % and 75.0 %, respectively. Conclusions PMX-DHP improved oxygenation and reduced the WBC count in patients with AE, with either steroids alone or steroids and cyclophosphamide. Further studies are required to verify the potential benefits of PMX-DHP for patients with AE of IP.